"The Possibility Of Applying The Ohlson Model To Assess The Shares Of Companies Listed On The Damascus Securities Exchange" (Latakia University Journal - Economic and Legal Sciences Series, 2020)
This research aims to demonstrate the possibility of applying the Ohlson model, to assess the shares of companies listed on the Damascus Securities Exchange (banks and insurance companies), by demonstrating the compatibility of the accounting data of these companies with the assumptions of this model,  and The ability of this model to  explain changes in the actual prices of this shares of those companies, and thus to indicate the acceptance of this model in the Damascus Securities Exchange to assess the shares of companies listed therein, As one of the most important models of accounting evaluation.To achieve this, this model was applied to the quarterly accounting data of banks and insurance companies that listed on the Damascus Securities Exchange (after excluding companies that do not meet the specific conditions for selecting the research sample), during the years 2014 - 2018.The results of the research during the period (2014 - 2018) showed, that the accounting data of the companies listed on the Damascus Securities Exchange (banks and insurance companies), are consistent with Ohlson model assumptions, in terms of achieving the extraordinary profits variable of the sample companies a first-class self-regression, As that The values ​​of the historical continuity coefficients for both the extraordinary profits and the other information variables of the sample companies is located within the range assumed by the model (not negative and less than one), The results also showed that the Ohlson model can explain the changes in the market prices of the shares of the companies listed on the Damascus Securities Exchange (banks and insurance companies) with a coefficient of 64%, and Thus the Ohlson model can be applied to assess the shares of the companies listed on the Damascus Securities Exchange (banks and insurance companies), The results also confirmed the importance of the evaluation role of the other information variable in the Ohlson model evaluation function, as this variable is the basic addition Presented by Ohlson in his model.